Educação para a saúde de diabéticos através dos círculos de cultura : uma estratégia de intervenção em enfermagem - Santos, Aliny de Lima (2011)
Diabetes mellitus (DM) can be defined as a chronic degenerative disease, caused by lack of insulin and / or inability of insulin to properly exercise its function. Need to control, there are changes in lifestyle, including food, adherence to physical exercise, and cessation of alcohol and cigarettes. Front these needs, is characterized as a disease hard to get along and adapt. Health education has been encouraged as a means of stimulating and maintaining control of the disease. Given the above, the objective was to implement a nursing intervention with people with diabetes mellitus using liberating pedagogy of Paulo Freire, through Circles of Culture. It is a descriptive, exploratory qualitative conducted with 26 type II diabetic subjects enrolled in the Diabetic Association of Maringa, aged 18 years. The 12 meetings took place in the association during the period May to July 2011, lasting 90 minutes. Were recorded in its entirety in MP3 player for later transcription of the speeches and so understanding, and field journaling. The transcripts were subjected to content analysis type theme. The results show that the greatest difficulty for diabetics is still the change in food, although the acceptance of the disease also influence the adaptation. Aspects such as social withdrawal, withdrawal, denial of illness and belief that it is best to eat what you want before the reality of death, also configured as inhibitors to control the disease. We also perceived that the family is to be the main support network and support for those who have the disease, and to participate in the meetings, were able to envision this network as well those who were there, sharing experiences. It was found that diabetics find it difficult to keep the disease under control and that the family concern with changing habits often appears as a secondary gain of illness, approaching them and making the patient feel more recognized in the home receiving more attention. Expressed satisfaction in participating in the Culture Circles, which encouraged them to make changes in their lives. The dialog presents itself as an effective way to facilitate the carrying DM for the accession of new habits and to develop and acquire attitudes of care and co-responsibility with the community. It contributes to the rapprochement between professional and patient through the construction of dialogic relations between the various actors in the scenario carefully. It is concluded that health promotion, especially when performed by groups of health education, directing individuals to seek not only health, but especially the best living with the disease and acceptance of necessary changes. It is noticed that, when performed through problem-based education, using dialogue and awareness, besides the best possible adaptation to the disease and support network, breaking the vertical relationship between the professional / patient, both approaching and so qualifying the care provided by adapting to the needs and realities of those involved through the exchange of knowledge and experiences.